Culturally Competent AI (Artificial Intelligence) and Robots for Transnational Caregiving and End-of-Life, and Ethical, Legal, and Social Issues - Hoshino, Kazumi; Siu, Loc (Bulletin of Asia-Pacific Studies, 2025)
This research analyzes AI (Artificial Intelligence) and robots for transnational caregiving for older adults and end-of-life. The research discusses culturally sensitive AI and robots and examines ethical, legal, and social issues of transnational caregiving for older adults and end-of-life. Based on the literature reviews, the research demonstrates policy implications of AI and robots for transnational caregiving for older adults and end-of-life; 1) Establish AI’s safety and effectiveness; 2) With the increasing availability of healthcare data and rapid progress in analytic techniques, AI tools transform healthcare sectors; 3) AI systems have access to sensitive personal information, necessitating robust legal and regulatory frameworks for safeguarding privacy, security, and integrity; 4) Control of the potentials of AI and robots; and 5) Minimize the risks of AI and robots.